Retrospective survival analysis of the use of uncemented modular tapered stems for revision in periprosthetic Vancouver B-type fractures. Is instability a threat to survival? - J. Lixa; P. Vieira; P. Pereira; A. Pinho; M. Seara; A. Sousa; L. Vieira (Revista Española de Cirugía Ortopédica y Traumatología)
Introduction and objectives: Periprosthetic hip fractures show increasing incidence and complexity, representing a challenge for the surgeon. We aimed to evaluate the survival of uncemented modular tapered stems in the treatment of periprosthetic Vancouver B2 and B3 type fractures and review the main complications and factors associated with decreased survival. Materials and methods: We performed a retrospective study of patients submitted to revision arthroplasty for treatment of periprosthetic femoral stem Vancouver B2 and B3 type fractures with an uncemented modular fluted tapered stem (MRP-Titan). Demographic and radiographic parameters were analyzed. The survival rate (free of reoperation) was calculated at 2- and 5-years using the Kaplan–Meier survivorship analysis. Results: Thirty-nine patients were included with a mean age of 73.5 years and a mean follow-up of 5 years. Arthroplasty survivorship at 2 years was 73.7% and at 5 years was 67.5% (mean 8.4 years; range 6.7–10.2). Survivorship was inferior in the patients with episodes of instability (mean 2.5 years; range 0–5.42) (p < 0.001). At least one episode of instability occurred in 26.3% of patients and 60% of these patients had a femoral head size 32 mm or lower. At least one episode of instability occurred in 71.4% of patients with a greater trochanter fracture (p = 0.008). The consolidation rate was 90.6% and the mortality rate was 23.7%. In the group of patients that died, 55.6% were submitted to at least one revision surgery (p = 0.044). Conclusion: Survivorship of an uncemented modular stem (MRP-Titan) in revision for PHF is significantly reduced by episodes of instability. Resumen: Introducción y objetivos: Las fracturas periprotésicas de cadera muestran una incidencia creciente. Nuestro objetivo fue evaluar la supervivencia de los vástagos modulares cónicos no cementados en el tratamiento de las fracturas periprotésicas tipo Vancouver B2-B3 y revisar factores asociados a una menor supervivencia. Métodos: Realizamos un estudio retrospectivo de los pacientes sometidos a artroplastia de revisión para el tratamiento de fracturas tipo Vancouver B2-B3 con vástago cónico estriado modular no cementado (MRP-Titan). Se analizaron parámetros demográficos y radiográficos. La tasa de supervivencia (libre de reoperación) se calculó a los 2 y 5 años mediante el análisis de supervivencia de Kaplan-Meier. Resultados: Se incluyeron 39 pacientes con una edad media de 73,5 años y un seguimiento medio de 5 años. La supervivencia a los 2 años fue del 73,7%, y a los 5 años, del 67,5% (media 8,4 años; rango 6,7-10,2). El 26,3% de los pacientes tuvieron al menos un episodio de inestabilidad y su supervivencia fue inferior (p < 0,001) (media 2,5 años; rango 0-5,42). De estos pacientes, el 60% tenían un tamaño de la cabeza femoral de 32 mm o inferior. El 71,4% de los pacientes con fractura del trocánter mayor presentaron al menos un episodio de inestabilidad (p = 0,008). La tasa de consolidación fue del 90,6% y la tasa de mortalidad fue del 23,7%. En el grupo de pacientes que fallecieron, el 55,6% fueron sometidos al menos a una cirugía de revisión (p = 0,044). Conclusiones: La supervivencia de un vástago modular no cementado (MRP-Titan) en revisión por FPH se reduce significativamente por episodios de inestabilidad.